Development Strategy of Intensive System of Vaname Shrimp (Litopenaeus vannamei) Cultivation Business at CV Jaya Tirta Vannamei, Probolinggo, East Java - Andi Rusdi Walinono; Rieke Nur Safitri; Ilyas (Systematic Literature Review Journal, 2025)
This study aims to analyze the development strategy of vannamei shrimp (Litopenaeus vannamei) cultivation business in the intensive pond system at CV Jaya Tirta Vannamei, Probolinggo, East Java. The research applied a qualitative descriptive approach combined with SWOT analysis to evaluate both internal and external factors affecting the business. Data were obtained through observation, interviews, and documentation, then processed to generate alternative development strategies. The results show that CV Jaya Tirta Vannamei possesses strong internal resources such as experienced human resources, reliable production facilities, and good management capabilities. Externally, the company benefits from the rising demand for vannamei shrimp in domestic and global markets, the availability of modern aquaculture technology, and supportive government policies. Nevertheless, some challenges exist, including fluctuating shrimp prices, vulnerability to disease outbreaks, and relatively high operational costs, which may influence business continuity if not addressed effectively. Based on the SWOT analysis, the most appropriate development strategy is the S-O (Strengths–Opportunities) strategy, with an alternative strategy score of 3.72. The recommended strategies are: (1) increasing shrimp production through the adoption of advanced and sustainable cultivation technology, (2) developing and maintaining a reliable water quality management system to enhance productivity, (3) utilizing skilled human resources to strengthen innovation in cultivation techniques, and (4) ensuring the availability of sufficient and quality feed to support continuous production growth. In conclusion, implementing the S-O strategy provides an effective pathway for CV Jaya Tirta Vannamei to optimize its internal strengths in response to external opportunities. By improving technology application, strengthening resource utilization, and enhancing production management, the company can secure competitive advantage, increase productivity, and ensure long-term sustainability in the rapidly growing aquaculture industry.